Abnormal cardiopulmonary exercise variables in asymptomatic relatives of patients with dilated cardiomyopathy who have left ventricular enlargement. Issue 5 (1st May 2000) - Mahon, N G; Sharma, S; Elliott, P M; Baig, M K; Norman, M W; Barbeyto, S; McKenna, W J
Abstract : BACKGROUND: Left ventricular enlargement with normal systolic function is common in asymptomatic relatives of patients with familial dilated cardiomyopathy, many of whom progress to overt dilated cardiomyopathy at follow up. OBJECTIVE: To examine maximal and submaximal gas exchange variables of cardiopulmonary exercise testing in asymptomatic relatives with left ventricular enlargement. DESIGN AND SETTING: Controlled evaluation of metabolic exercise performance of patients with dilated cardiomyopathy and asymptomatic relatives with left ventricular enlargement identified through prospective family screening in a cardiomyopathy outpatient clinic. METHODS: 23 relatives with left ventricular enlargement, 33 normal controls, 29 patients with dilated cardiomyopathy, and 10 elite athletes with echocardiographic criteria of left ventricular enlargement ("physiological" enlargement) underwent symptom limited upright cycle ergometry using a ramp protocol. RESULTS: Peak oxygen consumption (pV o 2 ; mean (SD)) was significantly reduced in relatives with left ventricular enlargement (78 (16.3)%) v normal controls (96%, p < 0.01) and athletes (152%, p < 0.001), but was higher than in patients with dilated cardiomyopathy (69%, p < 0.01). pV o 2 was less than 80% of predicted in 75% of patients, 58% of relatives, 22% of controls, and none of the athletes. Oxygen pulse (pV o 2 /heart rate) was less than 80% of predicted in 69% of patients, 35% of relatives, 6% of controls, and none of the athletes. The slope of minute ventilation v CO2 production (ΔVE/ΔV co 2 ) was > 30 in 68% of patients, 50% of relatives, and in none of the controls or athletes. Anaerobic threshold, occurring in relatives at 37 (14)% of the predictedV o 2, was higher than in the patients (32%, p < 0.01) and lower than in the controls (45%, p < 0.05) or in the athletes (55%, p < 0.001). CONCLUSIONS: Maximal and submaximal cardiopulmonary exercise test variables are abnormal in asymptomatic relatives with left ventricular enlargement, in spite of normal systolic function. This provides further evidence that left ventricular enlargement represents subclinical disease in relatives of patients with dilated cardiomyopathy. Metabolic exercise testing can complement echocardiography in identifying relatives at risk for the development of dilated cardiomyopathy.